Design of a mobile medical exoskeleton with balance support system - Fu, Chao. (2012)
The main objective of this Final Year Project was to design and fabricate a mobile medical exoskeleton with balance support system that capable of assisting patient with Spinal-Cord Injury (SCI) to walk. The final outcome of the project was to build an exoskeleton that would help the patient to complete his walking cycle without other people’s assistance.